Restrictive allograft syndrome after lung transplantation. (17th March 2021) - Klouda, Timothy; Vargas, Sara O.; Midyat, Levent
Abstract: Despite recent advances over the past decade in lung transplantation including improved surgical technique and immunotherapy, the diagnosis and treatment of chronic lung allograft dysfunction remains a significant barrier to recipient survival. Aside from bronchiolitis obliterans syndrome, a restrictive phenotype called restrictive allograft syndrome has recently been recognized and affects up to 35% of all patients with CLAD. The main characteristics of RAS include a persistent and unexplained decline in lung function compared to baseline and persistent parenchymal infiltrates on imaging. The median survival after diagnosis of RAS is 6 to 18 months, significantly shorter than other forms of CLAD. Treatment options are limited, as therapies used for BOS are typically ineffective at halting disease progression. Specific medications such as fibrinolytics are lacking large, multicenter prospective studies. In this manuscript, we discuss the definition, mechanism, and characteristics of RAS while highlighting the similarities and differences between other forms of CLAD. We also review the diagnoses along with current and potential treatment options that are available for patients. Finally, we discuss the existing knowledge gaps and areas for future research to improve patient outcomes and understanding of RAS.